Caracterização de painéis WPC fabricados com partículas de madeira de pinus e recicláveis de poliestireno - Vidrano, Bibiana Regina Argenta (2015)
Now a days, there is a worldwide tendency to value materials that, in addition to low cost, can be environmentally correct. This last condition refers to renewable, biodegradable and recyclable aspects that can be presented by the material. The production of new materials, such as wood-plastic panels (WPC, Wood Plastic Composite), with the recycling of waste is a market trend which aims at the same time achieve environmentally and ecologically correct products and reduce production costs. The aim of this study was to evaluate the possibility of producing WPC reusing polystyrene (PS) plastic cups combined with pinus wood, and test their physical and mechanical properties. The proportions of the polystyrene particles and wood particles employed were 75/25, 60/40, 50/50 and 40/60%. The performance of the panels was evaluated by determining the density, absorption and thickness swelling after 2 and 24 hours of water immersion, hardness, resistance to screws withdrawal, internal bond and bending. The addition of polystyrene tends to increase the dimensional stability of the panels, reducing water absorption and thickness swelling values. However density decreased thereof affecting other properties such as hardness, modulus of rupture (MOR) and modulus of elasticity (MOE). The tensile strength perpendicular to the board surface was higher in the panel with a higher content of (75/25%). Polystyrene reuse in the manufacture of composite wood-plastic was possible.